The role of elevation in moral judgment. Issue 2 (2nd April 2020) - Klebl, Christoph; Dziobek, Isabel; Diessner, Rhett
ABSTRACT: Elevation is the emotion elicited by witnessing acts of moral beauty and may be framed as the opposite of disgust. Two studies investigated the role of elevation in moral judgment and its relation to disgust. In Study 1 it was investigated whether elevation can attenuate the effects of disgust on moral transgression judgments. Participants were either induced to experience disgust (by giving them a bitter beverage), or to experience disgust and elevation simultaneously (by video induction). No effects of either emotion on moral transgression judgments were found. In Study 2 the nature of causal connectedness between elevation and moral virtue judgments was investigated by testing whether elevation amplifies moral virtue judgments. It was found that participants judged morally good acts as being more morally good when being elevated, suggesting that there is a bidirectional causal link between elevation and judgments of moral virtue.